HIV, HBsAg and HCV prevalences among voluntary blood donors in Mumbai: trends over a decade - Narayankar, Shilpa Laxmikant; Maindad, Vikas Chandrahas (International Journal of Research in Medical Sciences, 2019)
Background: With over 93 million donations made every year worldwide, blood transfusion continues to save millions of lives each year and improve the life expectancy and quality of life of patients suffering from life threatening conditions. At the same time, blood transfusion is an important mode of transmission of infection to the recipient. The present study was conducted to estimate the prevalence of HIV, HBV and HCV infections in voluntary blood donors at a tertiary care teaching hospital in Mumbai over a decade. Methods: All voluntary donors reporting to the blood bank were screened for HIV, HBsAg and HCV by using the appropriate enzyme linked immunosorbent assay. The study was designed for duration of ten years between January 2008 to December 2017. Medical reports of the donors were accessed from the blood bank records and analyzed. Results: A total of 8928 voluntary blood donors were screened. Amongst the blood donors, seropositivity of HBV (6% to 1.52 %) was highest followed by HIV (2.5% to 0.15%) then HCV (1.85% to 0.37%). Conclusions: Decreasing trends with low prevalence observed in the study is an encouraging sign supporting the growing awareness of these life-threatening diseases.